LA PRÉFIGURATION DU SPECTACLE D’OPÉRA - Diana TODEA (Studia Universitatis Babeş-Bolyai. Musica)
Departing from the idea that the opera is the most accomplished form of performance, this study proposes a review of its first manifestations. The purpose is that of clearifying the controversial evolution of the genre and the theatrical-musical forms that preceded it. In the beginning the opera was supposed to be a complete performance where the musical, literary, and spectacular elements would combine perfectly. Taking into consideration these basic characteristics, we intend to analyse and structure the main genres that led to the emergence of the opera. At the same time we underline the profile and the role held by music starting with the Ancient Tragedy to the latest form that foreshadows the opera performance – the dramatic madrigal.